The Role Of Simulators In Final Exams At Medical Universities: Revolutionizing Assessment In Healthcare Education (Texas Journal of Medical Science, 2024)
The integration of simulators into final exams at medical universities is transforming the way student competence is assessed. These advanced tools, which include high-fidelity mannequins, virtual reality (VR) simulations, and patient interaction models, allow for more realistic, standardized, and objective evaluations of students' clinical skills and decision-making abilities. By simulating real-world clinical scenarios, simulators provide a safer, more controlled environment for assessing critical skills such as diagnosing, performing procedures, and patient communication. This approach not only enhances the fairness and consistency of assessments but also better prepares students for the challenges of real-world medical practice. While there are challenges, including high costs and faculty training requirements, the use of simulators in medical final exams represents a valuable advancement in medical education. As technology continues to evolve, simulators will play an increasingly central role in shaping the future of healthcare training and assessment.